Place-Based Diminished Returns of Parental Educational Attainment on School Performance of Non-Hispanic White Youth - Assari, Shervin; Boyce, Shanika; Bazargan, Mohsen; Caldwell, Cleopatra H.; Zimmerman, Marc A. (Frontiers in Education, 2020)
Background: Educational outcomes of youth are a function of a wide range of factors including parental education level. This effect, however, is shown to be smaller for Black, Hispanic, and Asian American youth, a pattern called Marginalized Diminished Returns (MDRs). It is, however, unknown if it is race/ethnicity or other conditions associated with race/ethnicity (e.g. neighborhood quality) which reduces the returns of parental education for youth. Aim: To explore whether MDRs are only due to race/ethnicity or neighborhood quality, we compared the association between parental education level and adolescents’ school performance based on neighborhood quality. Methods: This cross-sectional study used wave 1 of the Add Health study, an ongoing nationally representative cohort, 1994-2019. Participants included 893 Non-Hispanic White adolescents between the ages of 12 and 21 years. The independent variable was parental education level. Age, grade, gender, and parental marital status of the parents were the covariates. The dependent variable was cumulative school grades in Math, English, History, and Science. Linear regression models were used for data analysis. Results: Overall, worse neighborhood quality was associated with a worse school performance, however, higher parental education level was not associated with better youth school performance in the pooled sample. We found a statistically significant interaction between parental education level and neighborhood quality suggesting that the association between parental education and youth school performance is smaller in poor neighborhoods. Conclusions: While high level of parental education level is a salient determinant of education outcomes for adolescents, this effect may be weaker in worse neighborhoods. The result suggests that MDRs may not be due to race/ethnicity but contextual factors that commonly covary with race/ethnicity. These contextual factors may include segregation, concentration of poverty, and other social and physical disorders in the neighborhoods.